#TITLE_ALTERNATIVE# - ANOM SYARIF MUCHSIN (NIM 13102088), FANZI
The Kamandanu train experienced wheel failure caused by thermal crack in surface. This broken wheel caused by thermal fatigue stress because of using composite brake not iron cast brake. Thermal fatigue stress is thermal tension stress that fluctuates more than yield strength material. It is happened. The impact loads were estimated using a mechanical analysis. To find a location and value of maximum stress using finite element method. The researchbegins with component failure observation to determine accident scenario. After it has has been determined, modeling stage and stretching analysis with finite element method were set. From the research, impact load for 12 cm flat that can caused crack initiation if train operate at minimum speed 38 km/hour. The estimation of wheel flat cycle to failure is 40 hour since flat occured.